2019
DOI: 10.1158/1538-7445.am2019-ct036
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT036: A phase I clinical trial of malignant pleural disease treated with regionally delivered autologous mesothelin-targeted CAR T cells: Safety and efficacy

Abstract: Background: Malignant pleural disease (MPD) from primary malignant pleural mesothelioma (MPM) or secondary metastatic disease (lung and breast cancers) affects more than 150,000 patients a year in the US alone. We developed chimeric antigen receptors (CARs) to target mesothelin (MSLN), a cell-surface antigen that we have shown is highly expressed in MPD, is associated with aggressiveness and poor survival, and has low expression in normal tissues. Methods: Using a second-generation CD28-costimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…Moreover, the intra-pleural treatment dose was 30-fold lower than the intravenous administered dose and elicited no grade III/IV toxicities. In a clinical setting, no'on-target, off-tumor' effects were seen when 21 patients with malignant pleural disease were treated with CD28-costimulated MSLN CAR-T cells intrapleurally (85,90,91). In this study 19 out of 21 patients had MPM, of whom 13 were subsequently treated with pembrolizumab (anti-PD1).…”
Section: Challenges For Car T-cell Therapy In Solid Tumorsmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, the intra-pleural treatment dose was 30-fold lower than the intravenous administered dose and elicited no grade III/IV toxicities. In a clinical setting, no'on-target, off-tumor' effects were seen when 21 patients with malignant pleural disease were treated with CD28-costimulated MSLN CAR-T cells intrapleurally (85,90,91). In this study 19 out of 21 patients had MPM, of whom 13 were subsequently treated with pembrolizumab (anti-PD1).…”
Section: Challenges For Car T-cell Therapy In Solid Tumorsmentioning
confidence: 82%
“…In this study 19 out of 21 patients had MPM, of whom 13 were subsequently treated with pembrolizumab (anti-PD1). In total two patients had a CR, five had PR and four had SD as best overall response (85). Just as for DC therapy, Combining CAR Tcell therapy with anti-PD1 treatment showed promising clinical results.…”
Section: Challenges For Car T-cell Therapy In Solid Tumorsmentioning
confidence: 99%
“…CAR T cells have been evaluated in early phase clinical studies for more than a decade, targeting a broad range of tumor antigens, including B7-H3, CAIX, CEACAM5, CD133, CD171, epidermal growth factor receptor (EGFR), EGFRvIII, FRa, GD2, GPC3, HER2, interleukin (IL)-13Ra2, mesothelin, MUC1, prostate-specific membrane antigen (PSMA), ROR1, and vascular endothelial growth factor (VEGF)-R2. 19,20,[22][23][24][25][26][71][72][73][74][75][76][77][78][79][80][81][82] Table 1 lists selected published studies, and Table 2 lists ongoing clinical studies. Early studies focused on first-generation CARs specific for CAIX, CD171, FRa, GD2, or IL-13Ra2.…”
Section: Car T Cells For Solid Tumors and Brain Tumors-clinical Expermentioning
confidence: 99%
“…[276][277][278] Checkpoint blockade/ CAR T cell therapy combinations are actively being pursued, 279 including the aforementioned clinical studies combining mesothelin-CAR T cells with pembrolizumab for the treatment of mesothelioma. 76 Furthermore, several studies have highlighted the benefit of combining radiotherapy with the administration of CAR T cells, and early clinical studies for patients with B cell lymphoma have produced encouraging results. 280 Recent preclinical studies have also demonstrated the benefit of boosting CAR T cells outside the immunosuppressive TME with amphiphile CAR ligands or RNA-based vaccines.…”
Section: Combinatorial Therapiesmentioning
confidence: 99%
“…A phase I study (NCT02414269) drawing on preclinical results in orthotopic mouse MPM models (120,121) is ongoing to test the MSLN-CAR-T cells in multi-treated MPM patients. Preliminary results presented at the AACR [Abstract CT036, (122)] and ASCO [Abstract 2511, (123)] meetings this year have shown an ORR and DCR of 36.8 and 57.8%, respectively, in a cohort treated off protocol in combination with pembrolizumab.…”
Section: Mesothelioma Targeting Antigensmentioning
confidence: 99%